2022
DOI: 10.1371/journal.pone.0268224
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on face masks and acne in a Nigerian population

Abstract: Background Acne vulgaris is a skin disorder that affects males and females with significant impact on quality of life. The onset of the COVID-19 pandemic led to a series of non-pharmaceutical interventions globally to reduce the spread of the virus particularly since there have been no known cures or definitive treatment for the disease. One key non-pharmaceutical intervention was recommendation on wearing of face masks. There are reports of discomfort associated with wearing face mask including complaints of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
2
21
1
2
Order By: Relevance
“…5 Study by Han et al, Ramesh et al and Shabari et al showed that the most reported symptoms of maskne were itching, pain, discomfort, stinging, sensation, burning sensation, dryness/tenderness, and excessive seborrhoea. 6,8,9,13 The most common signs were comedones, papules on cheek and nose, instead of nodules or cysts on forehead, submaxillary and neck. 5,8,13 Mask acne is thought to be a subtype of acne mechanica, for aggravation of the disease induced by an extrinsic factor that clearly intensifies acne, namely mechanical forces such are pressure, tension, friction, stretching, rubbing, pinching, or pulling, or almost any type of mechanical stress on the skin, although numerous other factors are implicated in its pathogenesis.…”
Section: Masknementioning
confidence: 99%
See 4 more Smart Citations
“…5 Study by Han et al, Ramesh et al and Shabari et al showed that the most reported symptoms of maskne were itching, pain, discomfort, stinging, sensation, burning sensation, dryness/tenderness, and excessive seborrhoea. 6,8,9,13 The most common signs were comedones, papules on cheek and nose, instead of nodules or cysts on forehead, submaxillary and neck. 5,8,13 Mask acne is thought to be a subtype of acne mechanica, for aggravation of the disease induced by an extrinsic factor that clearly intensifies acne, namely mechanical forces such are pressure, tension, friction, stretching, rubbing, pinching, or pulling, or almost any type of mechanical stress on the skin, although numerous other factors are implicated in its pathogenesis.…”
Section: Masknementioning
confidence: 99%
“…3,6,7 A person with prior history of acne vulgaris were about four times more likely to develop new acne lesions or experience worsening of their acne is logical and may be linked to their background predisposition to having acne prior to wearing face masks. 9 Studies proposed other risk factors may contribute to the development of acne, such as female HCW, younger HCW, those with a personal or family history of acne greater stress, the sleep deprivation HCW undergo during their shifts in COVID wards, and the consequent increasing in cortisol secretion. 4,15…”
Section: Risk Factormentioning
confidence: 99%
See 3 more Smart Citations